Students' perception at Universiti Kuala Lumpur (MIAT) on using animation in learning mathematics - Mohd Atan, Kamel Ariffin; Suncheleev, Rustem; Shitan, Mahendran; Mustafa, Mohd Shafie (Malaysian Educational Technology Association, 2007)
Recent years have seen an explosive development of IT Technologies. However, the problem of natural integration of modern technologies in teaching and learning mathematics is far from its final solution. In teaching Mathematics at universities these capabilities are either ignored or have extremely limited applications. Boyle (1997) proposed a systematic theoretical basis for educational multimedia design and according to him the central challenge for educational multimedia designers is creating interactive contents that promote effective learning. Bradley (2004) in his study observed that animated contents were superior to that of the text contents. In previous studies, the perception of students about animated technology in a public universities has been reported (Kamel Ariffin et. al., 2005). It would be of interest to know what is the perception of students in private institution and in this respect a survey was conducted in UniKL, Malaysian Institute of Aviation Technology (MIAT), comprising of students who had been exposed to an animated mathematics course. In this paper we describe our data and report our findings and also make a comparison between students’ perception in UPM and UniKL. Further a comparison is also made regarding perception of UniKL students from two different programmes of study.